The flora of the former Łęczyca iron ore dumps - Siciński, Jan; Sieradzki, Jarosław (Biodiversity: Research and Conservation, 2010)
Iron ore mines of the Łęczyca region started operating in the sixties and seventies of the 20th century and brought about considerable changes in the agricultural landscape of the town of Łęczyca and its vicinity. As a result of the ore exploitation, rock dumps as well as local depressions were created there. The subject of the present research was flora occurring in areas transformed by iron ore mining in the Łęczyca region. The flora is of spontaneous and anthropogenic (as a result of planting - reclamation) character. The results of the conducted research indicate that areas transformed by mining significantly increase their biological diversity.